Mimicking Photosynthesis with Supercomplexed Lipid Nanoassemblies Design, Performance, and Enhancement Role of Cholesterol - Wang, Mingming (Langmuir : the ACS journal of surfaces and colloids, 2016)
We report here a new approach to mimicking photosynthesis that relies on supercomplexed lipid nanoassemblies to organize small organic species for coordinated light harvesting, energy/electron transfer, and photo-to-electrochemical energy conversion. Specifically, we demonstrate efficient photoinduced electron transfer (PeT) between rhodamine and fullerene assembled together via electrostatically bound liposome and lipid bilayer hosts. The remarkable impact of the lipid matrix on the photoconversion efficiency is further revealed by cholesterol, whose addition is found to modify the distribution and organization of the coassembled rhodamine dyes and thus their photodynamics. This significantly expedites the energy transfer (ET) among rhodamine dyes, as well as the PeT between rhodamines and fullerenes. A respectable 14% photon-to-electron conversion efficiency was achieved for this supercomplexed system containing 5% rhodamines, 5% fullerenes, and 30% cholesterol. The morphology, photodynamics, and photoelectrochemical behavior of these lipid supercomplexes were thoroughly characterized using atomic force microscopy (AFM), fluorescence microscopy, steady-state and time-resolved fluorescence spectroscopy, and transient absorption (TA) and photoaction spectroscopy. A detailed discussion on enhancement mechanisms of cholesterol in this lipid-complexed photosynthesis-mimicking system is provided at the end